At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To factor the quadratic expression [tex]\(2x^2 - 14x + 24\)[/tex], we need to find its roots and then write the expression in its factored form.
1. Identify Coefficients:
The quadratic expression is in the form [tex]\(ax^2 + bx + c\)[/tex], where:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -14\)[/tex]
- [tex]\(c = 24\)[/tex]
2. Calculate the Discriminant:
The discriminant of a quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex] is given by [tex]\(\Delta = b^2 - 4ac\)[/tex].
[tex]\[ \Delta = (-14)^2 - 4(2)(24) = 196 - 192 = 4 \][/tex]
3. Find the Roots:
The roots of the quadratic equation can be found using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{\Delta}}{2a}\)[/tex].
[tex]\[ x = \frac{14 \pm \sqrt{4}}{4} = \frac{14 \pm 2}{4} \][/tex]
This gives us two roots:
[tex]\[ x_1 = \frac{14 + 2}{4} = \frac{16}{4} = 4 \][/tex]
[tex]\[ x_2 = \frac{14 - 2}{4} = \frac{12}{4} = 3 \][/tex]
4. Write the Factored Form:
With the roots [tex]\(x_1 = 4\)[/tex] and [tex]\(x_2 = 3\)[/tex], the quadratic expression can be factored as:
[tex]\[ 2(x - 4)(x - 3) \][/tex]
So, the factored form of the expression [tex]\(2x^2 - 14x + 24\)[/tex] is [tex]\(2(x - 4)(x - 3)\)[/tex], which corresponds to option:
C. [tex]\(2(x - 3)(x - 4)\)[/tex]
(Note that since multiplication is commutative, both [tex]\(2(x-4)(x-3)\)[/tex] and [tex]\(2(x-3)(x-4)\)[/tex] are correct and equivalent.)
1. Identify Coefficients:
The quadratic expression is in the form [tex]\(ax^2 + bx + c\)[/tex], where:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -14\)[/tex]
- [tex]\(c = 24\)[/tex]
2. Calculate the Discriminant:
The discriminant of a quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex] is given by [tex]\(\Delta = b^2 - 4ac\)[/tex].
[tex]\[ \Delta = (-14)^2 - 4(2)(24) = 196 - 192 = 4 \][/tex]
3. Find the Roots:
The roots of the quadratic equation can be found using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{\Delta}}{2a}\)[/tex].
[tex]\[ x = \frac{14 \pm \sqrt{4}}{4} = \frac{14 \pm 2}{4} \][/tex]
This gives us two roots:
[tex]\[ x_1 = \frac{14 + 2}{4} = \frac{16}{4} = 4 \][/tex]
[tex]\[ x_2 = \frac{14 - 2}{4} = \frac{12}{4} = 3 \][/tex]
4. Write the Factored Form:
With the roots [tex]\(x_1 = 4\)[/tex] and [tex]\(x_2 = 3\)[/tex], the quadratic expression can be factored as:
[tex]\[ 2(x - 4)(x - 3) \][/tex]
So, the factored form of the expression [tex]\(2x^2 - 14x + 24\)[/tex] is [tex]\(2(x - 4)(x - 3)\)[/tex], which corresponds to option:
C. [tex]\(2(x - 3)(x - 4)\)[/tex]
(Note that since multiplication is commutative, both [tex]\(2(x-4)(x-3)\)[/tex] and [tex]\(2(x-3)(x-4)\)[/tex] are correct and equivalent.)
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.